Into the long war : Oxford Research Group international security report 2006 - Rogers, Paul, 1943- (International security report, 2007)
"Iraq stands on the edge of civil war. As sectarian killings escalate, and troops become more deeply entrenched, is there any prospect of an exit strategy? Leading security expert Paul Rogers examines events in Iraq since May 2005 and how they impact on other countries including Afghanistan, Iran and the wider Middle East."--Goodreads